2013
DOI: 10.5230/jgc.2013.13.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Totally Laparoscopic Distal Gastrectomy after Learning Curve Completion: Comparison with Laparoscopy-Assisted Distal Gastrectomy

Abstract: PurposeThe aims are to: (i) display the multidimensional learning curve of totally laparoscopic distal gastrectomy, and (ii) verify the feasibility of totally laparoscopic distal gastrectomy after learning curve completion by comparing it with laparoscopy-assisted distal gastrectomy.Materials and MethodsFrom January 2005 to June 2012, 247 patients who underwent laparoscopy-assisted distal gastrectomy (n=136) and totally laparoscopic distal gastrectomy (n=111) for early gastric cancer were enrolled. Their clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 25 publications
2
33
0
1
Order By: Relevance
“…Therefore, the higher incidence of DSF in the laparoscopic approach should be interpreted as an effect of the normal learning curve in our experience, as it is also reported and well documented in several articles in literature [47][48][49][50].…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, the higher incidence of DSF in the laparoscopic approach should be interpreted as an effect of the normal learning curve in our experience, as it is also reported and well documented in several articles in literature [47][48][49][50].…”
Section: Discussionmentioning
confidence: 73%
“…For AGC, gastrectomy combined with D1 or D2 lymphadenectomy was more difficult than gastrectomy alone, which possibly resulted in the longer operation time in LG. However, according to studies that reported the learning curve of LG in AGCs, the operation time could reach a plateau after about 40 cases, and by experienced surgeons, LG could be done as quickly as OG [98][99][100].…”
Section: Discussionmentioning
confidence: 99%
“…However, these reports involved only small numbers of cases. When the outcomes of LTG and OTG are compared, the learning curve should also be considered [19,20]. Thus, the experience of the surgeons should be checked before a prospective study, including randomized clinical trials, to minimize bias resulting from operatorassociated factors [21].…”
Section: Discussionmentioning
confidence: 99%